Radiation Recall Dermatitis in Carcinoma Breast: A Decade of Experience from a Tertiary Cancer Center in North West India - Harsh, Kamlesh Kumar; Goswami, Vishal; Gajraj, Vikash; Kumar, Rajesh; Mohata, Shweta (Asian Pacific Journal of Cancer Care, 2025)
Aim: This study investigates the occurrence of radiation recall dermatitis (RRD), an acute inflammatory reaction triggered by chemotherapy in previously irradiated areas. RRD manifests in nearly two thirds of cases as skin reactions, ranging from mild erythema to severe desquamation. Our objective was to evaluate the frequency, severity and clinical pattern of RRD in breast cancer patients treated with radiotherapy. Materials and Methods: Data were retrospectively reviewed for 3462 breast cancer patients who underwent radiation therapy. Follow-ups were conducted weekly during chemotherapy, monthly for the initial 3 months, every 3 monthly up to 1 year, and biannually thereafter. The severity of dermatitis was graded using Radiation Therapy Oncology Group (RTOG) criteria, and supportive skin care was provided as needed. Patients included in the study had pathologically confirmed breast cancer, underwent modified radicle mastectomy, and received chest wall radiotherapy (40.05 Gy in 15 fractions; 2.67 Gy per fraction, 5 fraction per week for 3 weeks). Results: RDD was reported in 359 patients of 3462 (10.36%) following the administration of chemotherapy. The majority of cases (302 patients, 84.12%) occurred between 3rd week and the 2nd month post-chemotherapy. Grade 1 reactions were observed in 258 patients (71.86%), grade 2 in 85 patients (23.67%) and grade 3 in 16 patients (4.45%). Most RRD cases were associated with Adriamycin/doxorubicin, although other agents also agents also contributed. All patients responded favourably to topical steroids, with complete resolution and satisfactory skin appearance by 6 months. The latest reported case of RRD occurred 5 years post-radiotherapy and linked to administration of Paclitaxel and Carboplatin. Conclusion: This study highlights the frequency, timing and severity of RRD in breast cancer patients treated with radiotherapy and subsequent chemotherapy. While anthracyclines such as Doxorubicin are the most common culprits, other agents, including alkylating agents, antimetabolites and even exposure to UV light are also implicated. The unpredictable interval between radiotherapy and RRD onset, ranging from days to years, underscores the need for ongoing research to better understand this phenomenon.